An Empirical Examination of Store Attributes and Their Influence on Store Image Perception Among Organized Retail Food and Grocery Shoppers in Cochin, Kerala (International Journal of Food and Nutritional Sciences, 2022)
This empirical study delves into the realm of organized retail food and grocery shopping in Cochin, Kerala, focusing on the dynamic interplay between store attributes and store image perception among a sample of 200 shoppers. Informed by previous research, this study investigates how various store attributes impact shoppers' perceptions and preferences. The analysis employs statistical tools, including the Friedman Test, to assess the significance of these store attributes. The findings offer valuable insights for retailers looking to enhance their competitiveness and cater to the discerning tastes of Cochin's consumers in the organized retail sector.